Association between levobupivacaine and pancuronium. Interference in neuromuscular transmission and blockade in rats - Carvalho,Vanessa Henriques (2016)
ABSTRACT PURPOSE: To evaluate the effects of levobupivacaine on neuromuscular transmission and neuromuscular blockade produced by pancuronium in vitro. METHODS: Thirty rats were distributed into groups (n = 5) according to the drug used alone or in combination: Group I - levobupivacaine (5 µg.mL-1); Group II - pancuronium (2 µg.mL-1); Group III - pancuronium (2 µg.mL-1) + levobupivacaine (5µg.mL-1). The following parameters were evaluated: 1) amplitude of diaphragmatic response to indirect stimulation, before and 60 minutes after the addition of levobupivacaine and pancuronium alone, and after the addition of levobupivacaine combined with pancuronium; 2) membrane potentials (MP) and miniature endplate potentials (MEPP). RESULTS: Levobupivacaine alone did not alter the amplitude of muscle response and MP. In preparations previoulsy exposed to levobupivacaine, the block with pancuronium was significantly denser (90.2 ± 15.2%), showing a significant difference (p=0.031) in comparison to the block produced by pancuronium alone (48.9% ± 9.8%). There was a decrease in the frequency and amplitude of MEPPs. CONCLUSION: Levobupivacaine potentiated the neuromuscular blockade produced by pancuronium, confirming a presynaptic action by a decrease in miniature endplate potentials.